Occupational Safety and Health Leadership and Performance in Malaysian Industries - Suhaila Abdul Hamid ,; A. M Leman,; Norlia Goolamally,; Norshah Afizi Shuaib, (2020)
Leading and managing form the framework for skills and abilities that are necessary for an individual to drive team success. Occupational safety and health (OSH) Leadership modeled the organisational commitment in OSH and for the commitment to growth and sustained, it requires management support for employees OSH engagement. Both of the leadership and management support are addressed in the safety and health policy as stipulated in the Section 16 of Occupational Safety and Health Act 1994 to provide assurance on the OSH compliance as well as providing opportunity for employer to establish decent work through freedom from injury and ill health and provision of safe and healthy workplaces. The aim of this paper is to determine the influence of OSH management support in the relationship between OSH leadership and Safety Performance in Malaysian Industries in the context of organisational culture model. 300 responses who were OSH practitioners were collected from twelve different industries in Malaysia. Data were analysed using SPSS and AMOS. Results showed that having a leadership alone is not sufficient to improve OSH performance, it needs the mediation effect of OSH management support on OSH performances. (Abstract by authors)